Oxidation of micropollutants by visible light active graphitic carbon nitride and ferrate(VI): Delineating the role of surface delocalized electrons. (November 2022) - Pan, Bao; Zhou, Linxing; Qin, Jiani; Wang, Chuanyi; Ma, Xingmao; Sharma, Virender K.
Abstract: The treatment of recalcitrant micropollutants in water remains challenging. Ferrate(VI) (Fe VI O4 2−, Fe(VI)) has emerged as a green oxidant to oxidize organic molecules, however, its reactivity with recalcitrant micropollutants are sluggish. Our results demonstrate enhanced oxidation of carbamazepine (CBZ) by three types of visible light-responsive graphitic carbon nitride (g-C3 N4 ) photocatalyst in absence and presence of ferrate(VI) (Fe VI O4 2−, Fe(VI)) under mild alkaline conditions. The g-C3 N4 photocatalysts were prepared by thermal process using urea, thiourea, and melamine and were named as CN-U, CN-T, and CN-M, respectively. The degradation efficiency of CBZ, in both visible light-g-C3 N4 and visible light-g–C3 N4 –Fe VI O4 2- systems followed the order of CN-U > CN-T > CN-M. The mechanisms for this trend was elucidated by measuring physiochemical properties of the microstructures with various surface and analytical techniques. Results suggest the dominating role of specific surface area and surface delocalized electrons of microstructures in degrading CBZ. Crystallinity, morphology, and surface functional groups may not directly associate with CBZ degradation. The CN-U has higher specific surface area and surface delocalized electrons than CN-T and CN-M and therefore the highest degradation efficiency of CBZ. The surface electrons likely generated O2 ●- and 1 O2 in the visible light-g-C3 N4 system. The additional oxidants, Fe V and Fe IV in the visible light-g–C3 N4 – Fe VI O4 2− system led to higher degradation efficiency than the visible light-g-C3 N4 system. Results suggest that the surfaces of g-C3 N4 may be prepared preferentially with high levels of delocalized electrons at the surface of microstructures to enhance degradation of micropollutants. Graphical abstract: Image 1 Highlights: g-C3 N4 (CN-Urea (U), CN-Thiourea (T), and CN-Melamine (M)) are characterized. Degradation of CBZ is CN-U > CN-T > CN-M in g-C3 N4 and g–C3 N4 –Fe VI O4 2- system. g–C3 N4 –Fe VI O4 2- has higher CBZ degradation than g-C3 N4 under visible light irradiation. Surface delocalized electrons of g-C3 N4 microstructures reduce Fe VI O4 2- . Fe V /Fe IV species contribute to CBZ degradation in presence of Fe VI O4 2- .